The colour name composites in Ivan Drutch poetry (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with the colour name composites in Ivan Drutch poetic inheritance, their functionalities are revealed. Such derivatives assist creation of new poetic images, increase aesthetic, art-cognitive values of a poetic word.
Keywords: the colour names; composites; evaluative semantics